The environment as a theme in Malaysian art - Abdullah, Sarena (2012)
In recent decades in Malaysia, the subject of environment consciousness has become one of the main issues that has been raised by many people in Malaysia, from Non-Governmental Organisations (NGO) to various government bodies. In various ways, Malaysian artists have been affected by their realisation of the degradation of environmental qualities since the last thirty years. As such, this paper will focus and discuss more on the younger generation of artists such as Ahmad Shukri Mohamed, Nirmala Shanmughalingam, Redza Piyadasa, Bayu Utomo Radjikin, Ilham Fadhly Mohd Shaimy, Hamir Soib, Kok Yew Puah, Wong Hoy Cheong, etc. They are among the few artists that have been producing works that are either directly or indirectly addressing this significant issue in their artworks. This paper will discuss their works especially those that are visual documents of the thoughts and feelings of the Malaysian artists on urbanization process and environmental changes in relation to the increasing awareness and interests on environmental concerns following rapid urbanization in Malaysia. Apart from this, this paper will also discuss, the awareness of the issue itself as the main theme and subject selected by the artists; and secondly, the materials of the artworks themselves as tools or examples of how art work should lead by example, namely by using recycled materials, etc.